Pharmaco-Invasive Strategy With Half-Dose Tenecteplase in Patients With STEMI: Prespecified Pooled Analysis of Patients Aged ≥75 Years in STREAM-1 and 2 - Bainey, Kevin R.; Welsh, Robert C.; Zheng, Yinggan; Arias-Mendoza, Alexandra; Ristic, Arsen D.; Averkov, Oleg V.; Lambert, Yves; Kerr Saraiva, José F.; Sepulveda, Pablo; Rosell-Ortiz, Fernando; French, John K.; Musić, Ljilja B.; et al. (Circulation. Cardiovascular interventions, 2024)
BACKGROUND: In STREAM-1 (Strategic Reperfusion Early After Myocardial Infarction), excess intracranial hemorrhage occurred in patients aged ≥75 years receiving full-dose tenecteplase as part of a pharmaco-invasive strategy, whereas no further intracranial hemorrhage occurred after halving the tenecteplase dose. In STREAM-2 (Second Strategic Reperfusion Early After Myocardial Infarction), half-dose tenecteplase was an effective and safe pharmaco-invasive strategy in older patients with ST-segment-elevation myocardial infarction presenting within <3 hours, compared with primary percutaneous coronary intervention (PCI). We prespecified evaluating the efficacy and safety of a half-dose versus full-dose pharmaco-invasive strategy and compared the half-dose pharmaco-invasive strategy to primary PCI in patients aged ≥75 years. METHODS: We pooled data sets in patients aged ≥75 years from STREAM-1 and STREAM-2 receiving a pharmaco-invasive strategy versus primary PCI. Resolution of ST-segment-elevation after fibrinolysis and angiography was assessed, as was the relative risk of the primary composite of 30-day all-cause death, myocardial infarction, heart failure, and shock, along with bleeding. RESULTS: A total of 390 patients were included: 42 patients were randomized to full-dose pharmaco-invasive treatment, 205 patients to half-dose pharmaco-invasive treatment, and 143 patients to primary PCI. Half-dose versus full-dose pharmaco-invasive treatment resulted in similar proportions of patients achieving ≥50% ST-segment resolution posttenecteplase (63.2% versus 62.6%), with reduced intracranial hemorrhage (7.1% versus 0%, respectively). Half-dose pharmaco-invasive treatment and primary PCI also had similar proportions of patients with ≥50% ST-segment resolution postangiography (77.9% versus 72.4%; P=0.277) and comparable composite end points (23.4% versus 28.0%; relative risk, 0.90 [95% CI, 0.62-1.30]; P=0.567) without occurrence of intracranial hemorrhage. CONCLUSIONS: Comparable efficacy exists between half- and full-dose tenecteplase pharmaco-invasive treatments with improved safety in patients with ST-segment-elevation myocardial infarction aged ≥75 years. Half-dose pharmaco-invasive therapy is a legitimate therapeutic option for elderly patients with ST-segment-elevation myocardial infarction unable to access timely primary PCI. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00623623. URL: https://www.clinicaltrials.gov; Unique identifier: NCT02777580.